THE RESULTS OF LAPAROSCOPIC ILEAL URETERAL REPLACEMENT - B. K. Komyakov; B. G. Guliev (Вестник урологии)
Purpose. To evaluate the long-term results and effectiveness of laparoscopic ileal ureteral replacement. Material and Methods. To this study included the results of ileal ureteral substitution in 17 patients. In 10 patients we used open, in 7 patients used laparoscopic approach. Technique of operation (mobilization of ureter, ileal resection, creation of ureteroileal and ileobladder anastomoses) was similar in the both groups. We performed comparative analysis parameters, such as operative time, blood loss, narcotic analgesic, hospital stay and time to convalescence. Results. No conversion in patients who were underwent laparoscopic ileal replacement of ueter. Operative time was longer for 70 min in laparoscopic group, but this difference wasn’t significantly (p < 0,05). Narcotic analgesic use was dramatically less for the laparoscopic group than for the open group (40 mg versus 240 mg, p < 0,05). Hospital stay was significantly less in laparoscopic group (6 d versus 9 d, p < 0,05). Preoperative and postoperative serum creatinine, bicarbonate and chloride levels were unchanged for the laparoscopic and open groups. Moderate metabolic acidosis developed in 1 patient in open group. Time to convalescence was significantly less for the laparoscopic group (4 weeks versus 5,5 weeks, p < 0,05). Conclusion. Ileal ureteral substitution using laparoscopic approach is an effective and minimally invasive procedure. Compared with open procedures this technique allows to decrease trauma of surgery, hospital stay and time convalescence.